New VCs appointed for UiTM, UMPSA and UM - Jaayna, Jeevita (Star Media Group Berhad, 2023)
PETALING JAYA: Three new vice-chancellors have been appointed to lead Universiti Teknologi Mara (UiTM), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Universiti Malaya (UM).